Secondary electron emission characteristics of the Al2O3/MgO double-layer structure prepared by atomic layer deposition. Issue 7 (1st April 2021) - Cao, Weiwei; Wang, Bo; Yang, Yang; Zhu, Bingli; Guo, Junjiang; Xu, Peng; Bai, Xiaohong; Qin, Junjun; Wang, Chao; Zhu, Jingping; Bai, Yonglin
Abstract: As a secondary electron emission layer, an Al2 O3 /MgO double-layer structure is fabricated by atomic layer deposition (ALD) technology. The thickness range from 1 nm to 4 nm of the top Al2 O3 layer deposited on 20 nm MgO creates a double-layer. The morphology of the cross section, element distribution, surface roughness, X-ray diffraction, and secondary electron yield (SEY) values were measured by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), atomic force microscopy (AFM) and secondary electron emission (SEE) measurement systems. The SEE characteristics of the MgO single layer, Al2 O3 single layer and MgO/Al2 O3 double-layer were measured. The maximum SEY of a single MgO layer reached 6.2@600 eV, and the maximum SEY of a single Al2 O3 layer reached 3.92@400 eV. The SEY of the Al2 O3 /MgO double-layer decreased when the Al2 O3 thickness ranged from 1 nm to 4 nm, and the SEY reduction value of the double-layer decreased as the Al2 O3 thickness increased. Finally, Dionne's semiempirical SEE model was employed to explain the SEE yield of the prepared composite film structures. These results are useful for depositing a secondary electron emission layer in the channel of microchannel plates.